Single-molecule trapping and measurement in solution - Bespalova, M; Mahanta, S; Krishnan, M (Elsevier, 2019)
Trapping of a single molecule in the fluid phase was realized decades following developments in the gas-phase, because in some ways the solution phase posed a greater challenge. The key issues have since been addressed by several different means; techniques to confine nanometer scale entities in solution now abound and are gaining traction in a variety of single molecule studies. Available methods range from pure physical entrapment of a molecule on the one hand to electrokinetic and optical techniques, and approaches that exploit thermodynamic principles on the other. Some trapping techniques have also opened up new avenues to highly precise, accurate measurements of molecular physical properties in solution.